PEMANFAATAN SERAT LIMBAH SERAI DAPUR (CYMBOPOGON CITRATUS) SEBAGAI KERTAS SENI - Yusmini Murdiyah; Aprina Murwanti; Ataswarin Oetopo (Serat Rupa: Journal of Design, 2022)
Lemongrass plant (Cymbopogon citratus) is a spice plant that is commonly used and easily found in Indonesia. Besides being used in cooking and herbal drinks, lemongrass is also extracted into essential oil. At the household level, utilization of kitchen lemongrass can produce organic household waste. This is because not all parts of lemongrass can be used, such as the leaves and outer shell of the stem (Schmidt, 2020). Lemongrass is a plant in the Poaceae or grass family which has strong fiber characteristics and has high cellulose content (T. Cope, A. Gray, 2009). This knowledge ignites research ideas to utilize and process kitchen lemongrass plants, especially those in the form of waste into useful products. This idea is also in line with the movement launched by the Ministry of Industry of the Republic of Indonesia through its official online website, namely the Bangga Buatan Indonesia (BBI) (National Movement of Proud to be Made in Indonesia). The movement also seeks to develop and utilize local materials, one of which is natural fiber, as raw material for industry in Indonesia. The practice-based experimental-led method, a practice-based research led by experimentation (Sullivan 2005, 2006) was used in this study, then the result of experiments were analyzed using the parameters of folding and tear resistance.